MODELO DE ADMINISTRACIÓN DE SISTEMA INFORMÁTICO Y SU RELACIÓN CON LOS PROCESOS DE ATENCIÓN EN LA MUNICIPALIDAD DE VILLA EL SALVADOR - Palomino Rojas, Willy Alexis (2020)
The research is entitled "Computer System Administration Model and its relationship with the Attention Processes in the Municipality of Villa El Salvador" and the objective was to determine the relationship between the Information System Administration Model variable and the Attention Processes in the Municipality of Villa El Salvador. The research is quantitative, basic, correlational, descriptive, transectional. The population was made up of 25 workers and the convenience sample was made up of the total number of workers (25) of the municipality in question. For data collection, the questionnaire was used as an instrument for both study variables, which was subjected to an expert judgment. As a main conclusion, a direct and significant relationship was obtained between the Information System Administration Model variable and the Attention Processes with a p-value equal to 0.005 in the Municipality of Villa El Salvador Keywords: Information System Administration Model, Attention processes, Simplicity, Awareness, Directionality